Apple Role through Fair Labour Association (FLA) in order to Fixing Foxconn's Sweatshop in China - Sarah Puspa Sari (Parahyangan Center for International Studies, 2014)
In 2010, there is several news about suicides at Foxconn's factory in ShenZhen, China, a plant that assembles iPhones, iPods, and iPads for Apple. In order to fix this sweatshop practice in its chain, Apple make affliliateswith independent labor monitoring organizations engaged by the Fair Labour Association (FLA) as participating company. In FLA charter stated that the member should adopted a